2014
DOI: 10.1007/s11947-014-1451-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrostatic Pressure Processing on Texture and Color of Zebu Beef

Abstract: This study investigated the effect of hydrostatic pressure processing (HPP) on post-rigor mortis beef (Longissimus dorsi muscle, Nelore breed) relevant parameters, such as texture, cooking loss, and color. Pressures varying from 100 to 400 MPa at different times of pressurization (T1: time to reach set pressure, and T2: T1 plus 15 min) were applied, immediately followed by depressurization. Samples were evaluated for color, cooking loss, and tenderness. Both pressure level and pressurizing time had an effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…A previous study found that HPP at low temperatures (<30°C) increased meat toughness, and no significant changes were found in tenderness after aging [ 6 ]. In contrast, another study found that HPP at low temperatures lowered the shear force value of dark cutting beef [ 7 ], which agrees with the findings in Neto et al [ 8 ].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…A previous study found that HPP at low temperatures (<30°C) increased meat toughness, and no significant changes were found in tenderness after aging [ 6 ]. In contrast, another study found that HPP at low temperatures lowered the shear force value of dark cutting beef [ 7 ], which agrees with the findings in Neto et al [ 8 ].…”
Section: Introductionsupporting
confidence: 87%
“…Samples (n = 6) were treated at 300 and 500 MPa in a 350 L chamber (QFP 350L-600, Avure Technologies, Inc., Kent, WA, USA) using water as a pressurization medium at 15°C±2°C. Pressurization, holding, and depressurization times were 56.3 s, 180 s, and 12.2 s, respectively [ 8 ]. Samples were then stored under vacuum at 5°C±0.5°C for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Neto et al. () studied the effect of hydrostatic‐pressure processing (100 to 400 MPa for 15 min) on the texture and color of beef longissimus dorsi muscle. A significant reduction in the shear force of the samples pressurized at 100 and 200 MPa was observed with an increase of up to 21.12% in tenderness of samples treated at 200 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of HPP on raw meat products is uncommon due to high-pressure-induced protein denaturation and discoloration [10][11][12][13][14][15]. erefore, it is important to nd ways to stabilize the bright red color (oxymyoglobin) of fresh meat to develop a HPP-based pasteurization techniques for raw ground beef products.…”
Section: Introductionmentioning
confidence: 99%